Sustainable High-Rise Residential Building Development in Dhaka City - Begum, Halima; Supty, Sabrina Sharmin (The Jahangirnagar Review, 2024)
Efficient space utilization is essential due to urbanization, population growth, and urban sprawl, necessitating smart land use and vertical growth. Sustainable design serves as a benchmark for promoting responsible urban living. Over the last few decades, there is a pressing need for socially and environmentally sustainable high-rise residential building development to ensure healthy and comfortable urban settlements within limited space. This paper aims to examine aspects and strategies for such development. It is based on data collected from a household survey to assess residents’ living conditions in residential high-rises and from in-depth interviews with professionals that further provided valuable insights. It was found that the majority of the respondents supported high-rise development, while 66% of professionals recommend high-rises with six or more stories in Bangladesh, emphasizing environmental sustainability. Based on the findings a set of comprehensive strategies are proposed, focusing on current living conditions, and specific social and ecological aspects. The findings offer a potential model for promoting socially and environmentally sustainable high-rise housing in cities with diverse socioeconomic background, contributing to a more sustainable urban future.